(untitled) (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2025)
The global transformations that took place at the end of the 20th century had a direct impact on education policies, which came to be shaped by the logic of performativity within the neoliberal context. In this scenario, the ways in which categories are appropriated in scientific production are called into question. This article thus aimed to analyze how the category of performativity is used in studies on education policies in Brazil. To this end, meta-research was adopted as a theoretical-epistemological review method, based on theses and dissertations published between 2019 and 2024. The policies analyzed include evaluation policies, general policies, teacher education, and management, with a focus on the implications of the category for the subjects involved. The results indicate a tendency to approach performativity as a performance culture, based on Stephen Ball’s epistemological perspective, particularly drawing on the Policy Cycle Approach. It was found that the predominant epistemological positions are of a critical-analytical nature, although in some cases the use of concepts is insufficiently problematized, implying a certain scientific conformism regarding the concept of performativity. It is concluded that the appropriation of performativity in research lacks greater epistemological rigor with regard to conceptual clarity in the studies. Keywords: Education policy. Performativity. Meta-research.